Hormonal and genetic factors interact to control aromatase expression in the developing brain - Cisternas, Carla Daniela (2018)
Brain expression of the enzyme P450-aromatase has been studied extensively. Subsequent to the aromatisation hypothesis having established brain aromatase as a key factor to convert gonadal testosterone to oestradiol, several studies have investigated the regulation of aromatase during the critical period of brain sexual differentiation. We review previous and recent findings concerning regulation of aromatase. The role of gonadal hormones, sex chromosome genes and neurosteroids is analysed in terms of their contribution to aromatase expression, as well as implications for the organisational effect of steroids during development.